Peran Digital Linguistic dalam Optimalisasi Promosi E-Commerce UMKM Kuliner: Pendekatan Analisis Wacana Digital pada Coffee Shop di Garut - Qoriah, Desi; Muhammad Akbar, Dioka; Nurmalasari, Mutiana; Hilman Firmansyah, Muhamad; Septiana, Yosep (Institut Teknologi Garut, 2025)
In the era of the digital economy, language plays a strategic role in enhancing the visibility and success of Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector of coffee shops. However, many culinary MSME owners in rural areas such as Garut, West Java, still lack awareness and skills in using language effectively for digital marketing. This study aims to explore the concept of Digital Linguistic Capital by examining how language use on digital platforms influences customer engagement and business performance. This research employs a qualitative method using semi-structured interviews, discourse analysis of online content, and passive observation of several cafés and coffee shops in Garut. The findings indicate that most MSME owners intuitively use trendy and persuasive language, but they do not yet possess formal knowledge of SEO, brand linguistics, or stylistic consistency. MSMEs with strong linguistic strategies—such as emotional diction, persuasive expressions, and a consistent brand voice—demonstrate higher levels of customer interaction and digital visibility. In contrast, MSMEs with inconsistent language use experience low online engagement. The study concludes that digital linguistic capital is an essential yet underdeveloped asset. Strengthening digital communication skills and persuasive copywriting can enhance competitiveness as well as the cultural representation of coffee shop MSMEs in the digital marketplace. This research contributes to the development of a linguistics-based digital communication model for MSMEs.